2009
DOI: 10.1007/s10592-009-9842-z
|View full text |Cite
|
Sign up to set email alerts
|

General G ST and θ inflation due to biased intra-population sampling, and its consequences for the conservation of the Canarian Flora

Abstract: While knowledge of the degree of inter-population genetic differentiation underlies the understanding of microevolutionary processes in any organism, its calculation through G ST , F ST , or h (which, unlike the previous two, was designed to correct for unequal and small sample sizes) is often based in severely restricted intra-population samples, which are nonetheless tacitly assumed adequate to their accurate estimation. Empirical assessment of the influence of the number and intra-population distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Where possible, we collected a minimum of 10 samples per population. To reduce inflation in gene descriptors due to biased sampling (Caujapé‐Castells ), samples were collected from individuals scattered across the whole occupancy area of each population. DNA from 160 individuals and preserved in silica gel was extracted using the DNeasy Plant Mini Kit (QIAGEN Inc., Valencia, CA, USA), from 20 to 25 mg of silica‐gel‐dried leaves obtained from the fresh plant tissue collected from the field expeditions.…”
Section: Methodsmentioning
confidence: 99%
“…Where possible, we collected a minimum of 10 samples per population. To reduce inflation in gene descriptors due to biased sampling (Caujapé‐Castells ), samples were collected from individuals scattered across the whole occupancy area of each population. DNA from 160 individuals and preserved in silica gel was extracted using the DNeasy Plant Mini Kit (QIAGEN Inc., Valencia, CA, USA), from 20 to 25 mg of silica‐gel‐dried leaves obtained from the fresh plant tissue collected from the field expeditions.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, both studies called for more intensive conservation measures on the grounds that alterations of genetic connectivity could cause genetic homogenization, severe reductions in genetic diversity among populations, or hybridization (Francisco-Ortega et al, 2000). Nonetheless, estimates of high differentiation among natural populations in many published studies could be a spurious consequence of biased intra-population sampling, rather than a true representation of the biological characteristics of these insular floras (Caujapé -Castells, 2009a).Although the number of papers describing genetic variation in island populations has mushroomed in the last 10 years, very few of them include mainland congeners in comparisons. Hence, we lack robust measurements of the genetic depauperation of island taxa.…”
mentioning
confidence: 99%
“…The interpopulation apportionment of genetic variability, as inferred from Nei's G ST values (0.067 for C. tamadabensis and 0.126 for C. pritzelii ) and AMOVA results (Table ), indicate a high genetic cohesion within each species, in sharp contrast with the high fragmentation levels estimated for the Canarian flora ( G ST = 0.280; Francisco‐Ortega et al ., ). Caujapé‐Castells () and Pérez de Paz & Caujapé‐Castells () indicated that many of the average values of G ST reported by Francisco‐Ortega et al . () might be overestimates resulting from a restricted sampling in terms of the number and distribution of individuals.…”
Section: Discussionmentioning
confidence: 93%
“…are substantially higher than the averages for the Canarian endemics included in the review of Pérez de Paz & Caujapé‐Castells (), who emphasized the high genetic variability of the Canarian flora. Considering that many species included in that review were not sampled intensively, it is probable that the average genetic diversity in the Canarian flora is still much higher than reported [see Caujapé‐Castells () and Pérez de Paz & Caujapé‐Castells ()].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation